Preparation of Azido Polycarbonates via Bulk Polymerization of Halogenated Diols - St‐Charles, Jean‐Christophe; Dubois, Charles (Propellants, explosives, pyrotechnics, 2020)
Azido polymers find use as energetic binders in a variety of composite explosive and propellant applications, but few azido polyesters have previously been reported: a method is introduced for the preparation of two azido polycarbonates, poly(2,2’‐bisazidomethyl‐1,3‐propyl carbonate) and poly(3‐azido‐1,2‐propyl carbonate), possible binder candidates for energetics applications. The preparation method for these polymers involves a two‐step synthesis starting from the bulk polymerization of the commercially sourced diols with diphenyl carbonate in the presence of lanthanum (III) acetylacetonate as a neutral catalyst, and subsequent azidation in cyclohexanone. The physical and thermal characteristics of each are reported, indicating properties similar to other azido‐polymers. The thermal and mechanical properties of cured azido polyester resin mixtures are the subject of ongoing research.